Arabidopsis GAAP1 to GAAP3 Play Redundant Role in Cell Death Inhibition by Suppressing the Upregulation of Salicylic Acid Pathway Under Endoplasmic Reticulum Stress - Wang, Wei; Li, Xin; Zhu, Manli; Tang, Xiaohan; Wang, Zhiying; Guo, Kun; Zhou, Yan; Sun, Yue; Zhang, Wei; Li, Xiaofang (Frontiers in Plant Science, 2019)
The unfolded protein response (UPR) is activated to sustain cell survival by reducing misfolded protein accumulation in the endoplasmic reticulum (ER). The UPR also promotes cell death when the ER stress is severe. However, the underlying molecular mechanisms of UPR activity regulation and cell death transition are less understood in plants. Arabidopsis GAAP1 and GAAP3 are involved in the regulation of UPR and cell death. Five GAAP gene members are found in Arabidopsis. Here, we analyzed the function of GAAP2 in addition to GAAP1 and GAAP3 in ER stress response using single, double, and triple mutants. Results showed that single or double or triple mutants reduced plant survival and enhanced cell death under ER stress. And the sensitivity increased with the number of mutation genes increase. Quantitative real-time polymerase chain reaction analysis showed that mutation in triple genes promoted UPR signaling when confronted with mild ER stress, advanced SA target genes upregulation when confronted with severe stress. Moreover, Quantitative detection by UPLC-ESI-MS/MS showed that ER stress upregulated salicylic acid (SA) content in plants. These data suggest that GAAP1 to GAAP3 played redundant roles in cell death resistance and fine tuning UPR activation. And the anti-cell death function of GAAPs might be achieved by impairing the up-regulation of the SA pathway under ER stress.